PENGARUH RETURN ON ASSET, STRUKTUR MODAL, PRICE TO BOOK VALUE DAN GOOD CORPORATE GOVERNANCE TERHADAP RETURN SAHAM - Purnamaningsih, Dita; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi, 2014)
The purpose of this study was to determine the effect of return on asset (ROA), capital structure, and  price to book value (PBV) on stock return, as well as to determine the ability of good corporate governance (GCG) in moderating the effect of ROA, capital structure, and PBV on stock return. Capital structure is proxied by debt to equity ratio (DER) while GCG is proxied by corporate governance perception index (CGPI). The study was conducted at the listed companies in Indonesia Stock Exchange 2010-2012. Sample was determined by purposive sampling method, and found 11 companies as sample in this study. Data was processed by using multiple linear regression and moderated regression analysis techniques. Based on the results of multiple linear regression analysis is known that the capital structure and PBV have positive significant effect on stock return while ROA has not positive and significant effect on stock return. Based on the results of the moderated regression analysis is known that GCG is not a moderating variable that influence ROA, capital structure and PBV on stock return.
Keywords: CGPI, ROA, DER, PBV, stock return